ESTIMASI SUMBERDAYA NIKEL LATERIT DENGAN MEMBANDINGKAN METODE NEAREST NEIGHBOUR POINT DAN INVERSE DISTANCE WEIGHTING (Jurnal Geomine, 2016)
Calculation of resources plays an important role determining the amount of quality and ease of exploration commercially estimation method according to the geological conditions, the genesis and mineralization. This study aims to determine the total resource of nickel laterite using Nearest neighbour point (NNP) and Inverse distance weighting (IDW) method method, and to determine the factors that influence the result differences of the calculation using the two methods.According to the resource estimation with Niusing IDW method, it is obtained the tonnage resource is 2,540,953tons and the average grade is 1,85% Ni. Whereas the results of tonnage resources using NNP methodis 2,412,852tonnes with an average grade of 1,95 % Ni. The result differences of the total tonnage of nickel lateriteresource that obtained in Block “X” north Konawe is 128,101tons. Based on these calculations the obtained percent difference is 5 %. The main reason of the result differences of the resource estimation is the number of points in a block effect.Calculation of IDW method was conducted based on the nearest point to the estimated point.Whereas calculationof the NNP method considered the value in a block based on the nearest point to the block.